2020
DOI: 10.1186/s13011-020-00296-0
|View full text |Cite
|
Sign up to set email alerts
|

“Personal recovery depends on NA unity”: an exploratory study on recovery-supportive elements in Narcotics Anonymous Flanders

Abstract: Background: Mutual aid organizations, such as Narcotics Anonymous (NA), can provide support in substance use disorder (SUD) recovery processes. However, research on NA and its recovery-supportive elements is scarce and perspectives of NA-members remain understudied, in particular outside the US. Therefore, this study aims to gain insight into recovery-supportive elements of NA, as experienced by its members. Methods: To explore the perspectives on and experiences with recovery-supportive elements in NA, 11 in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…Narcotics Anonymous: NA) and alternative mutual aid groups (e.g. SMART recovery or other [local] types of recovery groups) have received far less public, professional and scientific attention and scrutiny (Dekkers, Vos, and Vanderplasschen 2020;White et al 2020;Zemore et al 2017). For example, no clinical trial has yet compared addiction treatment with and without NA involvement, despite most NA-studies involving treatment populations (White et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Narcotics Anonymous: NA) and alternative mutual aid groups (e.g. SMART recovery or other [local] types of recovery groups) have received far less public, professional and scientific attention and scrutiny (Dekkers, Vos, and Vanderplasschen 2020;White et al 2020;Zemore et al 2017). For example, no clinical trial has yet compared addiction treatment with and without NA involvement, despite most NA-studies involving treatment populations (White et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, an alternative explanation may be that love is representative of service users’ social support from families and broader social networks. Application of the CHIME-D (Connectedness, Hope, Identity, Meaning in life, Empowerment, Difficulties) personal recovery framework has foregrounded the importance of connectedness throughout recovery for 12-step recovery support group members [ 67 , 68 ]. It has also been demonstrated that relapse risk is considerably lower when a spouse or sponsor is supportive of one’s recovery process [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It consists of five positive elements important to recovery, namely, connectedness, hope, identity, meaning in life and empowerment (Leamy et al , 2011). Research has shown that not only are these five elements common to mental health recovery (Leamy et al , 2011; Stuart et al , 2016), they are also significant to the process of addiction recovery (Dekkers et al , 2020). Since its inception, the CHIME framework has seen adaptations such as CHIME-D and C-CHIME to expand on certain facets of recovery, for example, CHIME-D considers personal recovery in terms of the difficulties faced (Stuart et al , 2016; Dekkers et al , 2020), and C-CHIME looks at promoting recovery through creativity (Carson and Hurst, 2021).…”
Section: Methodsmentioning
confidence: 99%